2006
DOI: 10.1021/ja0651714
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Dinuclear Zn2+Complex and a Medium Effect Exerts a 1012-Fold Rate Enhancement of Cleavage of an RNA and DNA Model System

Abstract: The catalytic ability of a dinuclear Zn2+ complex of 1,3-bis-N1-(1,5,9-triazacyclododecyl)propane (3) in promoting the cleavage of an RNA model, 2-hydroxypropyl-p-nitrophenyl phosphate (HPNPP, 1), and a DNA model, methyl p-nitrophenyl phosphate (MNPP, 4), was studied in methanol solution in the presence of added CH3O- at 25 degrees C. The di-Zn2+ complex (Zn2 :3), in the presence of 1 equiv of added methoxide, exhibits a second-order rate constant of (2.75 +/- 0.10) x 10(5) M(-1) s(-1) for the reaction with 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
93
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 54 publications
10
93
0
Order By: Relevance
“…The systems containing one or more [12]aneN 3 units have shown prominent results in the detailed mechanism studies and excellent catalytic performance [16][17][18][19][20]. Recently we found that the dinuclear zinc(II) complex of 1,3-bis-[12]aneN 3 -propane accelerates the cleavage of model phosphate diesters by a remarkable factor of 10 12 -fold, when compared to the background reactions [21,22].With the above consideration, we report here on the syntheses and characterization of artificial nucleases containing mono-, di-and trinucleating [12]aneN 3 ligating units through click reactions between propargyl modified [12]aneN 3 and various azides.Our syntheses started from tri-tert-butyl-3-hydroxy-1,5,9-triazacyclododecane-1,5,9-tricarboxylate 1, which was prepared according to the literature reported by Lönnberg [16]. The synthetic route of the propargyl modified [12]aneN 3 compound, tri-tert-butyl-3-(prop-2-ynyloxy)-1,5,9-triazacyclododecane-1,5,9-tricarboxylate 2 is outlined in Scheme 1.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The systems containing one or more [12]aneN 3 units have shown prominent results in the detailed mechanism studies and excellent catalytic performance [16][17][18][19][20]. Recently we found that the dinuclear zinc(II) complex of 1,3-bis-[12]aneN 3 -propane accelerates the cleavage of model phosphate diesters by a remarkable factor of 10 12 -fold, when compared to the background reactions [21,22].With the above consideration, we report here on the syntheses and characterization of artificial nucleases containing mono-, di-and trinucleating [12]aneN 3 ligating units through click reactions between propargyl modified [12]aneN 3 and various azides.Our syntheses started from tri-tert-butyl-3-hydroxy-1,5,9-triazacyclododecane-1,5,9-tricarboxylate 1, which was prepared according to the literature reported by Lönnberg [16]. The synthetic route of the propargyl modified [12]aneN 3 compound, tri-tert-butyl-3-(prop-2-ynyloxy)-1,5,9-triazacyclododecane-1,5,9-tricarboxylate 2 is outlined in Scheme 1.…”
mentioning
confidence: 99%
“…The systems containing one or more [12]aneN 3 units have shown prominent results in the detailed mechanism studies and excellent catalytic performance [16][17][18][19][20]. Recently we found that the dinuclear zinc(II) complex of 1,3-bis- [12]aneN 3 -propane accelerates the cleavage of model phosphate diesters by a remarkable factor of 10 12 -fold, when compared to the background reactions [21,22].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…108,109 Thus, the capacity of this model complex However, it should not be underestimated that in addition to specific chemical features, the remarkable catalytic activity of phosphatase enzymes may also derive from the polarity and the steric demand of the environment of the active site. 273 It has been suggested that the catalysis of enzymes is promoted by binding of the substrate in hydrophobic pockets with an apparent dielectric constant much lower than the surrounding water. In this way, both the equilibrium for proton transfer reactions is shifted and the strengths of hydrogen bonds, involving the substrate binding and the transition state stabilization, are changed.…”
mentioning
confidence: 99%